Impact of Electrical Connection Distance on the Open Loop Modal Resonance of Grid Connected Photovoltaic Farms - Zhou, Bo; Shi, Peng; Xu, Yunyang; Zeng, Zhuolin (Frontiers in Energy Research, 2022)
The grid connection of photovoltaic (PV) farms may cause power system oscillations under the condition of open-loop modal resonance (OLMR). This study elucidated the origin of the induced low-frequency oscillations and examined the impact of the electrical distance between grid-connected PV farms on OLMR intensity by using a simplified real power network. A linearized state-space model of the real power system comprising grid-connected PV farms was derived. Based on this, an OLMR analysis was performed to examine the impact of the electrical distance between the grid-connected PV farms as well as between each grid-connected PV farm and the main grid. The OLMR analysis results indicate that the strength of the OLMR increases with the electrical distance between the PV farms, thereby leading to growing power oscillations. Moreover, the increase of electrical distance between each of the grid-connected PV farms and the main grid has a greater effect on OLMR intensity. Additionally, the non-linear simulations were performed to confirm the correctness of the OLMR analysis. Finally, by re-tuning the parameters of the control system of the grid-connected PV farms to reduce the phase-locked loop bandwidth, the OLMR can be effectively eliminated to avoid power oscillations.